Leukocyte-dependent effects of platelet-rich plasma on cartilage loss and thermal hyperalgesia in a mouse model of post-traumatic osteoarthritis. Issue 10 (October 2020) - Jayaram, P.; Liu, C.; Dawson, B.; Ketkar, S.; Patel, S.J.; Lee, B.H.; Grol, M.W.
Summary: Objective: Platelet-rich plasma (PRP) is an emerging therapeutic strategy for treatment of osteoarthritis (OA); however, there is a lack of preclinical and clinical evidence for its efficacy and its mechanism of action is unclear. In the current study, we utilized leukocyte poor-PRP (LP-PRP) and leukocyte rich-PRP (LR-PRP) to mimic clinical point of care formulations and assessed their potential to alter disease progression in a mouse model of post-traumatic OA. Method: Three-month-old wild-type male FVB/N mice received destabilization of the medial meniscus (DMM) surgery to induce OA. To assess the efficacy of LP-PRP and LR-PRP, mice were given intraarticular injections at 2-, 7- and 28-days post-surgery. Mice were then assessed at 5-, 9-, and 13-weeks post-surgery for changes in chronic pain using the hot plate nociceptive assay. At 14-weeks, OA pathogenesis was evaluated using histology and phase-contrast μCT. Results: Treatment with LP-PRP and to a lesser extent LR-PRP preserved cartilage volume and surface area compared to phosphate-buffered saline (PBS) as measured by phase-contrast μCT. However, both treatments had higher Osteoarthritis Research Society International (OARSI) and synovitis scores compared to sham, and neither substantially improved scores compared to PBS controls. With respect to thermal hyperalgesia, PBS-treated mice displayed reduced latency to response compared to sham, and LR-PRP but not LP-PRP improved latency to response at 5-, 9- and 13-weeks post-surgery compared to PBS. Conclusion: The results of this study suggest that effects of PRP therapy on OA progression and disease-induced hyperalgesia may be leukocyte-dependent. And while LP-PRP and to a lesser extent LR-PRP protect from volume and surface loss, significant pathology is still seen within OA joints. Future work is needed to understand how the different components of PRP effect OA pathogenesis and pain, and how these could be modified to achieve greater therapeutic efficacy.